Shining a light on posterior cortical atrophy. Issue 4 (14th January 2013) - Crutch, Sebastian J.; Schott, Jonathan M.; Rabinovici, Gil D.; Boeve, Bradley F.; Cappa, Stefano F.; Dickerson, Bradford C.; Dubois, Bruno; Graff‐Radford, Neill R.; Krolak‐Salmon, Pierre; Lehmann, Manja; Mendez, Mario F.; Pijnenburg, Yolande; et al.
Abstract: Posterior cortical atrophy (PCA) is a clinicoradiologic syndrome characterized by progressive decline in visual processing skills, relatively intact memory and language in the early stages, and atrophy of posterior brain regions. Misdiagnosis of PCA is common, owing not only to its relative rarity and unusual and variable presentation, but also because patients frequently first seek the opinion of an ophthalmologist, who may note normal eye examinations by their usual tests but may not appreciate cortical brain dysfunction. Seeking to raise awareness of the disease, stimulate research, and promote collaboration, a multidisciplinary group of PCA research clinicians formed an international working party, which had its first face‐to‐face meeting on July 13, 2012 in Vancouver, Canada, prior to the Alzheimer's Association International Conference.